2023
DOI: 10.1002/cctc.202300929
|View full text |Cite
|
Sign up to set email alerts
|

Upcycling of Polypropylene Wastes via Catalytically C−H Modification with Polar Olefins

Shuangjing Zhou,
Zongnan Zhang,
Rong Zeng

Abstract: While polypropylene (PP) is one of the most widely used polyolefin materials, its post‐functionalization has been a continuously researched topic in the polymer field since it could significantly improve physical and chemical properties by introducing polar groups, beneficial for development of the next generation of polyolefin materials. In this work, we describe the development of a visible‐light promoted, environmentally friendly iron‐catalyzed strategy and establishing of the reaction scope for C−H alkylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Combining excellent fluorescence characteristics with the compatibility of polar ester groups, LLDPE-MA-1 was used as a fluorescent compatibilizer for polystyrene (PS) and polypropylene (PP). , Binary blend PP/PS (80/20, w/w) and ternary blend PP/PS/ LLDPE-MA-1 (70/20/10, w/w/w) samples were prepared via solution blending (Page S89). EDS element distribution analysis showed that LLDPE-MA-1 was homogeneously dispersed in both phases (Figure a–c).…”
Section: Resultsmentioning
confidence: 99%
“…Combining excellent fluorescence characteristics with the compatibility of polar ester groups, LLDPE-MA-1 was used as a fluorescent compatibilizer for polystyrene (PS) and polypropylene (PP). , Binary blend PP/PS (80/20, w/w) and ternary blend PP/PS/ LLDPE-MA-1 (70/20/10, w/w/w) samples were prepared via solution blending (Page S89). EDS element distribution analysis showed that LLDPE-MA-1 was homogeneously dispersed in both phases (Figure a–c).…”
Section: Resultsmentioning
confidence: 99%
“…This modification can reduce the activation energy barriers for the C aliph –C aliph bonds adjacent to these polar elements during the photocatalytic process, thereby enhancing the efficiency of their activation and cleavage and resulting in a more diversified range of value-added chemicals. 125,126…”
Section: Caliph–caliph Activationmentioning
confidence: 99%